(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Lymphadenopathy is a very common clinical manifestation of many diseases. It is a disease of the lymph nodes, in which they are abnormal in size or consistency. The study intends to find out systematically the various pathological conditions presenting with enlarged lymph nodes in the neck, also the various nodes of clinical presentations and behavior of these conditions. This study consisted of 200 consecutive cases and diagnosis was made on the basis of clinical, fine needle aspiration cytology and histopathological findings. Out of 200 cases in the study 30.0% were non-specific lymphadenopathy, 47% were tuberculosis, 15% were secondary metastatic lymphadenopathy due to primary malignant lesion in head-neck region, 5% were primary malignant lesion that is lymphoma (Hodgkins and non-Hodgkins lymphoma), rest 3% were due to other lesions like Kikuchi’s disease, histiocytosis. After swelling in the neck, pain and fever were the most common presentations. Some patients presented with suppurative lymphadenopathy. In this study, fine needle aspiration cytology was found to be so reliable. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(1):29-32